Understanding Magnetization Dynamics of a Magnetic Nanoparticle with a Disordered Shell Using Micromagnetic Simulations - Aurélio, David; Vejpravova, Jana (Nanomaterials (Basel, Switzerland), 2020)
Spin disorder effects influence magnetization dynamics and equilibrium magnetic properties of real nanoparticles (NPs). In this work, we use micromagnetic simulations to try to better understand these effects, in particular, on how the magnetization reversal is projected in the character of the hysteresis loops at different temperatures. In our simulation study, we consider a prototype NP adopting a magnetic core-shell model, with magnetically coherent core and somewhat disordered shell, as it is one of the common spin architectures in real NPs. The size of the core is fixed to 5.5 nm in diameter and the shell thickness ranges from 0.5 nm to 3 nm. As a starting point in the simulations, we used typical experimental values obtained for a cobalt ferrite NP of a comparable size investigated previously. The simulations enabled us to study systematically the macrospin dynamics of the prototype NP and to address the interplay between the magnetic anisotropies of the core and the shell, respectively. We also demonstrate how the computational time step, run time, damping parameter, and thermal field influence the simulation results. In agreement with experimental studies, we observed that the direction and magnitude of the shell anisotropy influences the effective magnetic size of the core in the applied magnetic field. We conclude that micromagnetic simulations, in spite of being designed for much larger scales are a useful toolbox for understanding the magnetization processes within a single domain NP with an ordered spin structure in the core and partially disordered spins in the shell.
Keywords: hysteresis loop; magnetization dynamics; micromagnetic simulations; core-shell structure; magnetic nanoparticles; spin disorder